Changes in Plasma Lipid Profile as a Potential Predictor of Dengue Severity (The Insight, 2025)
Background: This study aimed to investigate changes in plasma lipid profile as potential predictors of disease severity in dengue infection. Methods & Materials: A prospective observational study was conducted on 120 laboratory-confirmed dengue patients, classified according to the WHO 2009 criteria as dengue without warning signs (n=52), dengue with warning signs (n=46), and severe dengue (n=22). Plasma lipid profile including total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglycerides during admission. Clinical and laboratory parameters were recorded, and their correlation with lipid levels were analyzed. Results: Significantly lower levels of total cholesterol, HDL, and LDL were observed in patients with severe dengue compared to those with milder forms (p
Keywords: Dengue; Severe dengue; Lipid profile; Cholesterol; HDL; LDL; Biomarker; Disease severity; Predictors